Quasispecies of SARS-CoV-2 revealed by single nucleotide polymorphisms (SNPs) analysis - Rongsui Gao; Wenhong Zu; Yang Liu; Junhua Li; Zeyao Li; Yanling Wen; Haiyan Wang; Jing Yuan; Lin Cheng; Shengyuan Zhang; Yu Zhang; Shuye Zhang; et al. (Taylor & Francis, 2021)
New SARS-CoV-2 mutants have been continuously indentified with enhanced transmission ever since its outbreak in early 2020. As an RNA virus, SARS-CoV-2 has a high mutation rate due to the low fidelity of RNA polymerase. To study the single nucleotide polymorphisms (SNPs) dynamics of SARS-CoV-2, 158 SNPs with high confidence were identified by deep meta-transcriptomic sequencing, and the most common SNP type was C > T. Analyses of intra-host population diversity revealed that intra-host quasispecies’ composition varies with time during the early onset of symptoms, which implicates viral evolution during infection. Network analysis of co-occurring SNPs revealed the most abundant non-synonymous SNP 22,638 in the S glycoprotein RBD region and 28,144 in the ORF8 region. Furthermore, SARS-CoV-2 variations differ in an individual’s respiratory tissue (nose, throat, BALF, or sputum), suggesting independent compartmentalization of SARS-CoV-2 populations in patients. The positive selection analysis of the SARS-CoV-2 genome uncovered the positive selected amino acid G251V on ORF3a. Alternative allele frequency spectrum (AAFS) of all variants revealed that ORF8 could bear alternate alleles with high frequency. Overall, the results show the quasispecies’ profile of SARS-CoV-2 in the respiratory tract in the first two months after the outbreak.
Keywords: Medicine; Molecular Biology; Evolutionary Biology; Environmental Sciences not elsewhere classified; Ecology; Biological Sciences not elsewhere classified; Infectious Diseases; Virology